A new intraocular lens marker to guide the implantation of toric intraocular lenses in small and mid-dilating pupils - Sri Ganesh; Sheetal Brar; Anwesha Chakma (Indian Journal of Ophthalmology, 2023)
Insufficient pupillary dilatation is a significant challenge during cataract surgery, as it increases the risk of various intraoperative complications. Implantation of toric intraocular lenses (TIOL) is particularly difficult in eyes with small pupils, as the toric marks are provided in the periphery of the IOL optic, making the visualization of the same difficult for proper alignment. Attempts at visualizing these marks using a second instrument such as a dialler or iris retractor lead to additional manipulations in the anterior chamber resulting in increased chances of postoperative inflammation and intraocular pressure rise. A new intraocular lens (IOL) marker to guide the implantation of TIOLs in eyes with small pupils is described, which can potentially be beneficial in achieving accurate alignment of toric IOLs in small pupils, without the need for additional manipulations, thus improving safety, efficacy, and success rates of TIOL implantation in these eyes.